A transfer mechanism for a monetary union - Philipp Engler; Simon Voigts (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2013)
We show in a dynamic stochastic general equilibrium framework that the introduction of a common currency by a group of countries with only partially integrated goods markets, incomplete financial markets and no labor migration across member states, significantly increases volatility of consumption and employment in the face of asymmetric shocks. We propose a simple transfer mechanism between member countries of the union that reduces this volatility. Furthermore, we show that this mechanism is more efficient than anticyclical policies at the national level in terms of a better stabilization for the same budgetary effects for households while in the long run deeper integration of goods markets could reduce volatility significantly. Regarding its implementation, we show that the centralized provision of public goods and services at the level of the monetary union implies cross-country transfers comparable to the scheme under study.
Keywords: F41; F44; E2; E3; E52; 330; monetary union; asymmetric shocks; fiscal policy; fiscal transfers